Research Progress of Treatment of Black and Odorous Water Bodies with Aeration Technology - WU Zuojingtong; DAI Xianpu; WU Hui; PAN Hongzhong (Renmin Zhujiang)
When treating black and odorous water bodies,the current aeration technology is faced with problems such as unscientific aeration design,unreasonable design of parameters such as aeration volume,aeration time,and influence radius,and unclear mechanism of coupling with other technologies.To solve these problems,this paper conducts a literature study of the effect of aeration in reducing common pollutants in water bodies and clarifies the effectiveness of aeration in the treatment of black and odorous water bodies.Then,factors affecting the aeration effect are comprehensively analyzed,and the following conclusions are drawn from the results.Bottom microbubble aeration has significant advantages in effect and energy consumption;clear correlations among aeration intensity,aeration time,and pollutant removal rate are observed;when energy consumption and effect are comprehensively considered,the room for optimization of aeration/non-aeration ratio remains large.Finally,an overview and prospects of the coupling study of aeration and other technologies are presented.This research is expected to provide a theoretical reference for the treatment of black and odorous water bodies with aeration technology.